J19 Paving the way for a Promising PDE10 drug with an Enzyme Occupancy Study, A 28 Day Safety Study Assessing Corticostriatal Activity and a 6 Month Safety and Efficacy Study in HD Patients. (17th September 2014) - Delnomdedieu, M; Vitolo, O; Pickering, E; Duvvuri, S; Berger, Z; Murphy, M; Papapetropoulos, S; Zaleska, Margaret M
Abstract : There is no approved treatment providing multi-domain (motor, behaviour, cognition) symptomatic control in HD. Phosphodiesterase10A (PDE10A) is an emerging therapeutic target highly enriched in striatal medium spiny neurons. Its inhibition results in increased striatal levels of cGMP and cAMP leading to overall increased striatal activation and decreased behavioural activity. Preclinical findings obtained by CHDI in R6/2 and Q 175 transgenic mouse lines suggest that PDE10A inhibitor (PDE10i) treatment may lead to functional normalisation of affected brain circuitry and improve motor, cognitive and behaviour symptoms in HD patients. A 28 day study in HD patients is assessing safety and multi-symptom domain effects of PDE10Ai in HD patients. In addition to traditional clinical motor and cognitive measures, treatment effects are assessed using fMRI, behavioural tasks, quantitative motor tests and apathy, during this 28 day double-blind study with 20 mg bid PDE10Ai or placebo (n = 32, 1:1 ratio). 5 mg bid or placebo (2:1) may also be tested. Efficacy endpoints include change from baseline to Day 28 in percent BOLD signal change for reward related activity, Grip Strength Incentive Motivation task, resting state ASL, QMotor parameters, UHDRS Total Motor Score and Apathy. A PET enzyme occupancy study is enrolling up to 3 cohorts of 4 male HVs using radiotracer [18F]MNI-659. First cohort received 20 mg single dose. Measured%EO will guide next cohort dose (1 mg to 30 mg). Expected%EO (based on preclinical estimates) at 20 mg is ˜42–59%. A POC Phase 2 study in HD patients will randomise ˜260 patients to 5, 20mg PDE10i BID, or placebo (1:1:1 ratio) to assess efficacy of 26-week dosing on motor function (primary), chorea severity and overall clinical impression (secondaries). Pfizer's HD program is designed to test safety, tolerability and efficacy in HD patients, determine clinical translatability of preclinical observations of rescued corticostriatal function, and provide confidence for continued clinical development of the compound for multi-domain symptomatic treatment of HD.